(untitled) (Research, Society and Development, 2021)
Objectives: to address the role and actions of nursing in human reproduction its importance in the psychological and technical support of patients who go through the stages and procedures of AHR. Methods: this is an integrative literature review study with a qualitative and exploratory approach focused on the importance of the role and actions of nurses in AHR. Results: the role of nursing in Assisted Human Reproduction goes beyond technical subjectivity and brings human, interpersonal and care aspects in the involvement of the entire process, as the professional who spends more time in contact with the patient, he/she must provide the necessary assistance for the couple, being the main channel between the patients and the specialist, the nurse guides, prepares and actively participates in the techniques of AHR. Conclusion: nurses must demonstrate training and theoretical knowledge involved in constant research and updates, provide their patients with care, attention, motivation and respect in the treatment of infertility in human beings, with the nursing team being the direct and fast channel between patients and experts in the entire RHA process.